Potential of Pathway Partnerships with High Schools - Terri Gaeddert (Academic Chairpersons Conference Proceedings, 2023)
Presenter and participants will discuss current and emergent trends among colleges and universities in working with high school students. Presenter will share one approach to developing partnerships and career pathways with communities and school districts. Data from three semesters of implementation will be shared.
Keywords: enrollment; cost of higher education; dual credit; college to career; changing demands